(untitled) (Dhaka University Journal of Science, 2016)
Swelling behaviors of crosslinked acrylamide (AAm)/carboxymethyl cellulose sodium salt (CMC) blend hydrogels synthesized using gammaradiation from Co-60 source in aqueous solutions of urea were investigated. The parameters like effect of radiation dose and concentration of CMC in AAm/CMC blend were studied on swelling properties. Swelling experiments were performed in various concentrations of urea solution and distilled water at room temperature. The swelling properties of hydrogels increased with increased concentration of CMC but it decreased with increased radiation dose. Hydrogels showed enormous swelling in aqueous solution of urea. The swelling properties of AAm/CMC hydrogel were lower in distilled water than that of in urea solution. The water absorption of AAm/CMC blend hydrogels increased from 4,800 to 9,000% for the concentration range of CMC from 0 to 7% for 48 hours standing in distilled water at 25 kGy radiation dose. It was also found that water absorption by AAm hydrogel with 7% CMC decreased from 13,800 to 8,500% for the radiation range from 15 to 35 kGy for 48 hours standing time in water. The equilibrium water content (EWC) of AAm/CMC blend hydrogel depended on radiation dose. EWC decreased from 0.9935 to 0.9896 with the variation of radiation dose from 15 to 35 kGy in 0.01M urea solution at 48 hours. Dhaka Univ. J. Sci. 64(2): 105-108, 2016 (July)